Período de interferência de plantas daninhas na cultura da cenoura em dois sistemas de irrigação localizada - Reginaldo, Laís Tereza Rêgo Torquato (Universidade Federal Rural do Semi-Árido, 2019)
The carrot (Daucus carota L.) is one of the main cultivars in Brazil, however, weed interference represents one of the factors that have the greatest impact on the reduction of crop productivity. Therefore, the objective of this work was to determine the interference periods for the "Suprema" carrot cultivar cultivated in two localized irrigation systems. The experiment was installed at the Rafael Fernandes experimental farm of the Federal Rural Semi-Arid University, Mossoró-RN, between July and November 2018, the experimental design was a randomized complete block design with three replications in the plots scheme subdivided. The plots consisted of the two irrigation systems (drip and micro sprinkler), and the subplots corresponded to the duration of living with the weeds in the treatments, being divided into two groups, consisting of periods of control (in the clean) or coexistence (in the bush ) of the weeds with the crop. The beginning and the end of the critical period of interference prevention (PCPI), based on a yield loss of 2.5, 5 and 10% tradable carrot, was determined by fitting the Sigmoidal model 4 parameters to the relative production data . As there was an increase in acceptable loss the critical period of interference prevention (PCPI) was reduced. The weed population composition was higher at the beginning of the carrot development cycle, with a decrease in the population density and the number of dominant species at the end of the crop cycle. The presence of the weed community throughout the crop cycle can lead to losses of up to 97.5% in productivity. The PCPI varied for the irrigation systems used. The carrot cultivation with and without competition under the micro sprinkler irrigation system presented higher productivity compared to the cultivation in the drip system. In the drip irrigation system the PCPI was 23 DAE and in the irrigation system by micro sprinkler was 7 DAE, considering yield losses of 5%. The length (3.3 or 1.0 weeks) of the PCPI in the carrot was affected by the irrigation systems
Monografia
Keywords: Daucus carota L.; Microaspersão; Gotejamento; Período de interferência; Competição; Daucus carota L.; Microaspersion; Drip; Interference period; Competition; CIENCIAS AGRARIAS::AGRONOMIA